Associations between Anxiety, Depression, and Poor Quality of Sleep on the Risk of Irritable Bowel Syndrome: A Meta-Analysis - Cendekia Airedeta Mulianda; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2023)
Background: Risk factors for Irritable Bowel Syndrome (IBS) are mental disorders such as anxiety and depression, while sleep disorders affect 50% of patients with IBS. The condition of IBS if it is chronic can have a negative impact on quality of life and work productivity. The purpose of this study was to estimate the relationship between anxiety, depression and poor sleep quality with the risk of irritable bowel syndrome by means of a systematic review and meta-analysis study.Subjects and Method: This article was prepared using systematic review and meta-analysis studies. This study uses the PICO Model. Meta-analytic studies were conducted by searching for articles from databases in electronic form using Google Scholar, PubMed, Springerlink, Sciencedirect, and the Cochrane Library. An article search was conducted on 15-30 October 2022. The keywords used were “irritable bowel syndrome” or “IBS” or “Functional gastrointestinal disorder” or “Anxiety” or “Depression” or “Mental Disorders” or “Psychological stress” or “Sleep quality” or “Sleep disturbances” or “Cross-Sectional”. The inclusion criteria for this study were complete articles using a Cross-Sectional study, with the year of publication 2009-2022. Analysis of the articles in this study used RevMan 5.3 software.Results: A total of 30 cross-sectional studies from Asia were selected for systematic review and meta-analysis. The data collected shows that anxiety increases 1.53 times and depression 1.29 times with the risk of IBS while poor sleep quality increases the risk of IBS by 1.80 times. This data is considered statistically significant. The results showed that Anxiety (aOR=1.53; 95% CI=1.23 to 1.90; p=0.001), Depression (aOR=1.29; 95% CI=1.05 to 1.59; p=0.02), Poor sleep quality (aOR=1.80; 95% CI=1.48 to 2.19; p<0.001).Conclusion: The relationship between anxiety-depression mental disorder and poor sleep quality is felt to be statistically significant in causing irritable bowel syndrome. Keywords: irritable bowel syndrome, risk factors, anxiety, depression, sleep quality Correspondence:Cendekia Airedeta Mulianda. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: c.airedeta@gmail.com. Mobile: +6282336712311.